Heavy Metal Pollution in Olives Grown in Bursa, Turkey - SAHAN, YASEMIN; BASOGLU, FIKRI (Asian Journal of Chemistry, 2010)
Heavy metal pollution is one of the most important environmental problems. The toxic effects of metals and their accumulation throughout the food chain lead to serious ecological and health problems. In this study, the accumulation of lead, cadmium, iron, copper and zinc in olives (Olea europaea) collected from a field situated near busy roads and industrial areas was investigated. Samples were collected at distance of 5-20 m from the road. Olive samples were obtained from 90 orchards in Mudanya, Gemlik and Orhangazi (Bursa, Turkey). Atomic absorption spectrophotometer (AAS) was used to determine these metals. The mean of Pb, Cd, Fe, Cu and Zn levels were found in the studied samples were 1362.23 ± 4.94 μg/kg-wet weight(ww), 158.29 ± 1.12 μg/kg-ww, 66.37 ± 2.03 mg/kg-ww, 6.51 ± 0.79 mg/kg-ww and 5.76 ± 0.79 mg/ kg-ww, respectively.